A contingent valuation of the biomitigation benefits of integrated multi-trophic aquaculture in Canada. Issue 1 (2nd January 2016) - Martinez-Espiñeira, Roberto; Chopin, Thierry; Robinson, Shawn; Noce, Anthony; Knowler, Duncan; Yip, Winnie
ABSTRACT: Integrated multi-trophic aquaculture (IMTA) is the farming, in proximity, of aquaculture species from different trophic levels and with complementary ecosystem functions. IMTA allows one species' uneaten feed and wastes, nutrients, and by-products to be recaptured and converted into fertilizer, feed, and energy for the other crops. By taking advantage of synergistic interactions between species, IMTA can help aquaculture evolve towards more responsible and sustainable systems. This study uses data from a contingent valuation survey to provide an estimation of the non-use benefits that, in the form of biomitigation of the external costs imposed on the marine environment, would be derived by Canadians from the adoption of IMTA for Atlantic salmon aquaculture. We find the benefits accruing to households who do not purchase salmon habitually would range between about 43 million/year and about 65 million/year for the next five years, depending on the treatment of 'don't know' responses to the payment question.